Influence of scanning velocity on Co24.7Cr5Mo5.4W alloy built via selective laser melting on roughness properties - Ahmed Al-Aloosi, Raghad; Taha, Ziad A.Taha; Onur ÇOMAKLI, Onur ÇOMAKLI (Iraqi Journal of Laser, 2026)
The utilization of Selective Laser Melting (SLM) in the production of intricate metal items has gained significant attention in the medical and dental sectors. Products created using SLM must possess surfaces that exhibit a high degree of smoothness. The objective of this research is to examine the impact of various laser process parameters, specifically the scan rate and hatch spacing, on the surface roughness of Co-Cr dental alloys fabricated in three dimensions (3D) by selective laser melting (SLM) technology. The results indicate that a scanning speed of 700 mm/s yields superior surface morphology and microstructure. The parameter investigation conducted in this paper resulted in the attainment of relative densities as high as 98.9% for the additively built workpieces. The present study focuses on investigating surface roughness in Co–Cr alloys fabricated using powder metallurgy techniques, namely selective laser melting.